Sensitive timing of undifferentiation in oligodendrocyte progenitor cells and their enhanced maturation in primary visual cortex of binocularly enucleated mice. - Hyeryun Shin (Public Library of Science (PLoS), 2021)
Sensory experience modulates proliferation, differentiation, and migration of oligodendrocyte progenitor cells (OPCs). In the mouse primary visual cortex (V1), visual deprivation-dependent modulation of OPCs has not been demonstrated. Here, we demonstrate that undifferentiated OPCs developmentally peaked around postnatal day (P) 25, and binocular enucleation (BE) from the time of eye opening (P14-15) elevated symmetrically-divided undifferentiated OPCs in a reversible G0/G1 state even more at the bottom lamina of the cortex by reducing maturing oligodendrocyte (OL) lineage cells. Experiments using the sonic hedgehog (Shh) signaling inhibitor cyclopamine in vivo suggested that Shh signaling pathway was involved in the BE-induced undifferentiation process. The undifferentiated OPCs then differentiated within 5 days, independent of the experience, becoming mostly quiescent cells in control mice, while altering the mode of sister cell symmetry and forming quiescent as well as maturing cells in the enucleated mice. At P50, BE increased mature OLs via symmetric and asymmetric modes of cell segregation, resulting in more populated mature OLs at the bottom layer of the cortex. These data suggest that fourth postnatal week, corresponding to the early critical period of ocular dominance plasticity, is a developmentally sensitive period for OPC state changes. Overall, the visual loss promoted undifferentiation at the early period, but later increased the formation of mature OLs via a change in the mode of cell type symmetry at the bottom layer of mouse V1.